2021
DOI: 10.1212/nxi.0000000000001041
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis

Abstract: Background and ObjectivesTo investigate the total circular RNA (circRNA) profile in patients with relapsing-remitting multiple sclerosis (RRMS) and healthy controls (HCs).MethodsHybridization microarray was used to define the circRNA profile in peripheral blood mononuclear cells (PBMCs) from 20 untreated patients with RRMS (10 in relapse and 10 in remission) and 10 HCs. We analyzed close to 14,000 individual circRNAs per sample. The discovery set data were validated using quantitative reverse transcription-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…They are critical regulators in the immune system, and are specifically expressed in specific organs, tissues, or cells. Accumulating evidence has highlighted the crucial potentials of circRNAs as diagnostic and therapeutic markers in multiple autoimmune diseases, including systemic lupus erythematosus (SLE), multiple sclerosis (MS), and RA [9][10][11]. Nevertheless, little is known of the effects and mechanism of circRNAs in regulating immune cell polarization and immune homeostatic imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…They are critical regulators in the immune system, and are specifically expressed in specific organs, tissues, or cells. Accumulating evidence has highlighted the crucial potentials of circRNAs as diagnostic and therapeutic markers in multiple autoimmune diseases, including systemic lupus erythematosus (SLE), multiple sclerosis (MS), and RA [9][10][11]. Nevertheless, little is known of the effects and mechanism of circRNAs in regulating immune cell polarization and immune homeostatic imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…Upon analyzing the expression results of AK2 and IKZP3, an upregulation of gene transcription was found (P = 5.65E-22, FC = 3.1; P = 1.72E-17, FC = 3.0, respectively). 84 CircRNAs as biomarkers for disability score in MS. Zurawska et al after found a circRNA biomarker that was associated with disability score. The group analyzed the downregulated circRNAs in the RRMS-relapse versus the RRMS-remission group versus HC.…”
Section: Differences In Circrna Expression Between Ms Patients and He...mentioning
confidence: 99%
“…In addition to circRNAs being implicated in the pathogenesis of MS, they have also been linked to disease activity. Accordingly, three (hsa_circRNA_101348, hsa_circRNA_102611, and hsa_circRNA_104361) circRNAs targeting 15 miRNAs and three additional protein-coding RNAs (of which 2 AK2 and IKZF3 are known to be involved in B-cell function) were measured to be overexpressed during a relapse [ 443 ]. The disease activity-related expression of various circRNAs was corroborated by a subsequent study, which has additionally described the sex-dependent increase of circRNA expression in MS, and furthermore has validated and proposed six additional circRNAs as potential biomarkers [ 431 ].…”
Section: Fluid Biomarkers Of Multiple Sclerosismentioning
confidence: 99%